Physical and functional properties of banana pseudostem flour and its effect on the quality (texture and microstructure) of formulated bread - Hoon, Ho Lee; Norlia, Muhamad; Thuan-Chew, Tan; Noor Aziah, Abdul Aziz (2017)
The objectives of this study were to compare physical and functional properties of banana pseudostem flour (BPF) with commercial wheat flour (CWF). The texture and microstructure qualities of composite breads formulated with partial substitution (10%) of CWF by BPF, as well as the addition of hydrocolloids, i.e. xanthan gum or sodium carboxymethyl cellulose (Na CMC), were also investigated. The microstructure of the bread crumb was evaluated using scanning electron microscope. When compared to CWF, water and oil holding capacities for BPF was significantly (p < 0.05) higher, whereas bulk density, water activity, and lightness (CIE L*) value for BPF was significantly (p < 0.05) lower. Bread formulated with BPF without addition of hydrocolloids showed harder bread crumb than the bread containing BPF and hydrocolloids. However, the addition of Na CMC into the composite bread formulation showed to improve the crumb softness, whereby the crumb appeared to have more continuous protein network and larger gas cells. Therefore, composite bread with added Na CMC is suitable to be utilized in processing of good quality bread.